1995
DOI: 10.1093/carcin/16.5.1141
|View full text |Cite
|
Sign up to set email alerts
|

Frequent p53 alterations but low incidence of ras mutations in UV-B-induced skin tumors of hairless mice

Abstract: We have investigated UV-B-induced skin tumors of hairless SKH-HRA mice for alterations in the p53 gene and for mutations in either of the three ras genes. Out of 32 tumors screened, only one contained a ras mutation, i.e. in codon 12 of the K-ras gene. Alterations in the p53 gene were much more abundant, as illustrated immunohistochemically by the accumulation of p53 protein in 75% of the tumor sections examined. Immunoreactivity was observed primarily in the proliferative cell compartment, but no clear correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
2
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 0 publications
6
72
2
2
Order By: Relevance
“…The prevalence of p53 protein overexpression in UV-induced skin cancer ranged from 20% to 80% in previous reports (Nagano et al, 1993;van Kranen et al, 1995van Kranen et al, , 1997Berg et al, 1996;Nataraj et al, 1996). The significant positive rate in Bowen's disease patients suggested that p53 gene mutation commonly occurred in the early stages of arsenic-related skin cancer.…”
Section: Discussionmentioning
confidence: 89%
“…The prevalence of p53 protein overexpression in UV-induced skin cancer ranged from 20% to 80% in previous reports (Nagano et al, 1993;van Kranen et al, 1995van Kranen et al, , 1997Berg et al, 1996;Nataraj et al, 1996). The significant positive rate in Bowen's disease patients suggested that p53 gene mutation commonly occurred in the early stages of arsenic-related skin cancer.…”
Section: Discussionmentioning
confidence: 89%
“…UV-induced skin tumors in NER-proficient mice expressed a very typical mutation spectrum at p53. The great majority of the mutations are found at dipyrimidine sites at the non-transcribed strand (NTS) [114], [115], [116], [117], [118] and [119]. In NER-deficient mice, the prevalence of p53 mutations in the TS versus NTS is dependent on the specific pathway which is absent.…”
Section: Skinmentioning
confidence: 99%
“…A role for sun exposure in the induction of the p53 mutations is indicated by the notion that the mutations are almost exclusively C to T or CC to TT transitions at dipyrimidine sites, both hallmarks of UV-induced DNA damage (Brash et al, 1991;Kress et al, 1992;Kanjilal et al, 1993;Ziegler et al, 1993). Moreover, in an animal model, frequent alterations in the p53 gene have been noticed in tumours caused by UV-B treatment (Kanjilal et al, 1993;van Kranen et al, 1995).…”
mentioning
confidence: 99%